2021
DOI: 10.4103/jhrs.jhrs_241_20
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide Has Adverse Effects on Human Sperm Quality Parameters, Induces Apoptosis, and Reduces Survival

Abstract: Background: One of the causes of male fertility disorders is the exposure of oxidative stress on the human sperm. Understanding the mechanism of disturbance is important to develop a better treatment for infertile or subfertile patients. Aims: The aim of this study was to analyze the effects of hydrogen peroxide (H 2 O 2 ) on human sperm quality parameters and cell survival. Settings and Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 31 publications
0
12
0
2
Order By: Relevance
“…Tis positive correlation between CAT activity and sperm motility can be explained by the importance of this enzyme in the protection of sperm from potentially toxic ROS levels [25]. Treatments with H 2 O 2 produced an increase in MDA levels and Te Scientifc World Journal 3 inhibited advanced sperm motility parameters [26]. However, the incubation of human sperm H 2 O 2 revealed that human catalase was able to counteract the adverse efects of H 2 O 2 on sperm motility [12].…”
Section: Discussionmentioning
confidence: 99%
“…Tis positive correlation between CAT activity and sperm motility can be explained by the importance of this enzyme in the protection of sperm from potentially toxic ROS levels [25]. Treatments with H 2 O 2 produced an increase in MDA levels and Te Scientifc World Journal 3 inhibited advanced sperm motility parameters [26]. However, the incubation of human sperm H 2 O 2 revealed that human catalase was able to counteract the adverse efects of H 2 O 2 on sperm motility [12].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies can also be found in the case of H 2 O 2 treatment. In each of these, a decrease in the viability of sperm cells, deterioration of the kinetic parameters, reduced capacitation and penetration ability, and increased lipid peroxidation can be observed [85,86].…”
Section: Hydrogen Peroxidementioning
confidence: 99%
“…•− formation, H 2 O 2 exposures were applied as a direct OS source, and t-BuOOH treatments were performed to cause the peroxidation of lipids [77,86,88]. The samples of both groups were aliquoted into Eppendorf tubes (300 µL/tube) and the following treatments were performed: (i) 0 mM, 1 mM, 2 mM, and 5 mM H 2 O 2 , (ii) 0 mM, 1 mM, 2 mM, and 5 mM menadione, (iii) 0 mM, 1 mM, 2 mM, and 5 mM t-BuOOH.…”
Section: Artificial Ros Inductionmentioning
confidence: 99%
“…The overproduction of NO has been observed in infertile women and men with varicocele. Common forms of ROS that affect sperm survival and its function include H 2 O 2 , OH• [ 23 , 24 ], peroxyl radicals, and hypochlorite ions [ 25 , 26 ]. ROS-induced damage to carbohydrates and lipids leads to the formation of ketoamines and ketoaldehydes [ 27 ], alkyl radicals, such as malondialdehyde (MDA), and 4-hydroxynonenal (HNE) (i.e., biomarkers of lipid peroxidation), respectively [ 28 ].…”
Section: Oxidative Stressmentioning
confidence: 99%